THE EFFECT OF THE PROJECT BASED LEARNING MODEL WITH A VISIT HOME APPROACH AND LEARNING STYLE ON IPS LEARNING OUTCOMES IN ELEMENTARY SCHOOL - Nurhasanah; Samsidar Tanjung; Siman (Sensei International Journal of Education and Linguistic, 2022)
This research aims to:(1) To find out the difference in social studies learning outcomes of students who are taught using the project based learning model assisted by the visit home method compared to the online learning model; (2) To find out the differences in social studies learning outcomes of students who have visual, auditory, and kinesthetic learning styles; (3) To determine the interaction between the learning model and student learning styles on student social studies learning outcomes. The sample in this study was class V students consisting of 2 class groups, namely VA as many as 27 students and class VB as many as 27 students. Collecting data through learning outcomes tests and student learning style questionnaires. The data analysis technique used is descriptive and inferential statistical techniques. The results showed that: (1) There were differences in the social studies learning outcomes of students who were taught using the project based learning model assisted by the visit home method compared to online media (Fcount = 7.686 and sig. 0.008 > 0.08); (2) There are differences in social studies learning outcomes between students who have visual, auditory, and kinesthetic learning styles (Fcount = 4.539 and sig. 0.008 > 0.16); and (3) There is an interaction between learning approaches and learning styles on students' social studies learning outcomes (Fcount = 6.703 and sig. 0.008 > 0.03).